Prospective Brides’ Experiences of Reproductive Health and Premarital Care: A Scoping Review - Fitri, Fitri; Hakimi, Mohammad; Sulistyaningsih, Sulistyaningsih (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Reproductive health and premarital services are important aspects of marriage preparation to prevent health hazards for the bride and groom. There are still many prospective brides who have limited knowledge about reproductive health and the benefits of premarital screening and counseling. Low utilization of premarital services can increase the risk of pregnancy complications, sexually transmitted infections, as well as early marriage, which poses a high risk to maternal and child health. This study aims to explore the experiences of prospective brides related to reproductive health and premarital services through a systematic review using the scoping review method.Method: This study employed a scoping review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) Flowchart approach. The literature search was performed in the main databases such as PubMed, ScienceDirect, and Wiley, using keywords determined based on the PEOS (Population, Exposure, Outcome, and Study Design) framework. The literature review was conducted on scientific publications in English, primary research articles or reviews relevant to the same theme, as well as studies published within the last 10 years. In addition, it was analyzed thematically to identify patterns of key findings.Result: The level of knowledge of future husbands and wives’ reproductive health and premarital services still varies, with most individuals having limited understanding before undergoing educational interventions. Interventions such as premarital courses, counseling, and brochure-based counseling are effective in improving the knowledge and attitudes of future husbands and wives. However, there are barriers to the implementation of premarital services, such as limited access, social stigma, and a lack of rules regulating obligatory premarital examinations. Therefore, stronger policies are needed from the government, as well as ongoing education in schools and universities to increase public awareness of the importance of reproductive health before marriage.